Процесс коммуникации в клинической диагностике. Семиотический подход - Долгополов, И.Н. (Кибернетика и системный анализ, 2009)
Досліджено природу знаку, його функції, особливості знаків ситуації в клінічній діагностиці, а також різні аспекти трансперсональної комунікації. Розглянуто об’єктивні ознаки–знаки, симптоми, їх словесні позначення, необхідні для переведення діагностичної інформації з рівня сигналів на рівень повідомлення шляхом виокремлення сенсу в процесі їх розуміння. The nature of a sign, its functions, distinctive features of a sign situation in clinical diagnostics, and also various aspects of transpersonal communications are investigated. Objective attributes such as signs, symptoms, and their verbal denotations are considered that are necessary to translate diagnostic information from the level of signals to the level of a message by extraction their meaning during their understanding.